Situações de saneamento ambiental do turismo no espaço rural: estudo do caso da Rota Germânica - Jasper, Juliana Rose (My University, 2014)
The rural area passed by a redefinition in agriculture and in the cattle-breeding sectors in the world and also in Brazil, configuring new activities and functions non-agricultural as the tourism. The several possibilities of tourism in the rural area help in the settlement of the man in the country, improve the life quality and the self-esteem besides contributing with the revitalization and preservation of the environment and the local culture. However, to get success the management including the environmental has a fundamental importance. Therefore, it s necessary that the projection selects the sanitation. In this way, it s important to know the environmental sanitation conditions of the rural area in the sense to define public politics for the projection of Turistic Routes. To identify the environmental sanitation conditions was chosen the Germanic Route that unite 14 turistic undertakings of the rural area. To collect information was utilized a questionnaire applying the direct interview and personal techniques with opening and closed questions. The present study is of exploratory character with qualitative and quantitative analysis. The results made possible to identify that the rural acres that work with tourism envolved in the Germanic Route invested in sanitation, but it isn t expressive. As well as was identified the necessity of evaluation programs and monitorament of the water potability, reduction of the water consume and the minimization of residues. Concerning the drainage, the undertakers mention that they put into practice the appropriate treatment. They also mention the control necessity of the vectors. In this way, to administer the projection and the management of the supportable tourism, due to complexity of the turistic activity and the environment where it occurs, are essential all the knowledges, envolving a multidisciplinal group.
O meio rural passou por uma redefinição no setor agropecuário tanto no mundo como no Brasil, configurando novas atividades e funções não-agrícolas, como por exemplo, o Turismo. As diversas possibilidades de turismo no espaço rural podem auxiliar na fixação do homem no campo, melhora a qualidade de vida e a auto-estima, além de contribuir com a revitalização e preservação meio do ambiente e da cultura local. Entretanto para obter êxito a gestão inclusive a ambiental, são de fundamental importância. Logo, é necessário que o planejamento contemple o saneamento. Desta forma, é necessário conhecer as condições de saneamento ambiental do espaço rural no sentido de definir políticas públicas para o planejamento de Rotas Turísticas. Para identificar as situações de saneamento ambiental foram selecionas a Rota Germânica, que engloba 14 empreendimentos turísticos do espaço rural. Para a coleta de dados foi utilizado um questionário estruturado, utilizando-se da técnica de entrevistas diretas, pessoais, com perguntas abertas e fechadas. O presente estudo é de caráter exploratório, com análise qualitativa e quantitativa. Os resultados possibilitaram identificar que as propriedades rurais que trabalham com turismo envolvidos na Rota Germânica investiram em saneamento, porém não é expressivo. Assim como, foi identificado a necessidade de programas de avaliação e monitoramento da potabilidade da água, de redução do consumo de água e de minimização de resíduos. Em relação ao esgoto, os empreendedores apontam que realizam o tratamento adequado para o mesmo. Também apontam a necessidade de controle dos vetores. Desta forma, para dar conta do planejamento e da gestão do turismo sustentável, devido a complexidade da atividade turística e do meio onde ocorre, são indispensáveis todos os saberes, envolvendo uma equipe multidisciplinar.
Keywords: Turismo; Planejamento; Espaço Rural; Saneamento ambiental; Rota Germânica (RS); Tourism; Projection; Rural area; Ambiental sanitation; Germanic Route (RS); Planejamento turístico